Evaluation Study of Kedunglarangan River To Protect Flood In Pasuruan and Sidoarjo - Ni Nyoman Adum M (Journal of Applied Science, Engineering, Technology, and Education, 2019)
Construction of the Kedunglarangan river flood control system designed to prevent flooding every rainy season in the Bangil sub-district. Kedunglarangan River is a river that flows in two regencies Sidoarjo and Pasuruan which has an area of 282.67 km2 watershed with a river length of 23.7 km. Kedunglarangan river has 4 (four) watershed sub-systems. The scope of this flood prevention work-study is the normalization of the Kedunglarangan River starting from the meeting with the Wrati River downstream up to 7 km. Normalization work is carried out with excavation and river widening to meet flood discharge in accordance with the conditions of the study area. If the river excavation work is done in accordance with the design master will form a basin that causes the creation of a dike. In this condition, it will be a temporary water reservoir where the water velocity is very low. So the work carried out the impact is only temporary. From the results of analysts, it is more efficient to do river widening and embankment raising rather than increasing river depth. River excavation work like that is very risky to create very fast sedimentation. Normalization method with river widening is one way to maintain the river flow downstream and flood water levels